Promotion Strategy Analysis On Non Wage Recipients That Turning Into The Participant Of The Labor's Health Insurance Administering Agency Of Makassar Branch - Fuji Astuti; Firman Umar; Risma Niswaty; Muhammad Guntur; Muh Darwis; Fatmawada S (Pinisi Business Administration Review, 2021)
This research is a qualitative descriptive study. The purpose of this research is to find out how the promotion strategy for non-wage recipients becomes a participant of the Labors’ Health Insurance Administering Agency (BPJS Ketenagakerjaan) of Makassar branch, as well as what are the supporting and inhibiting factors for the promotion strategy of non-wage recipients who become the participants of BPJS Ketenagakerjaan of Makassar branch. The informants in this study were the Head of Marketing for Non-Wage Recipients, Marketing Associates for Non-Wage Recipient Participants, and Non-Wage Recipient Workers. The data was collected through observation, interviews, and documentation. Data analysis techniques is using data reduction techniques (data reduction), data display (data presentation), and conclusions drawing / verification. The results showed that BPJS Ketenagakerjaan of Makassar branch only used four of five forms of promotional strategies, namely advertising, sales promotion, public relations, and personal selling. The supporting factors in the promotion strategy for non-Wage recipients to become the participants of the BPJS Ketenagakerjaan of Makassar Branch are doing cooperation with stakeholders and protection agents as well as support from government agencies. Meanwhile, the inhibiting factors are the lack of public awareness and understanding of the importance of the benefits of the BPJS Ketenagakerjaan as well as the relatively low level of education of non-wage recipients. By improving the promotion strategy it is very important to increase public understanding on the importance of the Labors’ Health Insurance Admnistering Agency Program for socio-economic protection, especially for non-wage recipients.